"Bike litter" and obligations of the platform operators: Lessons from China's dockless sharing bikes. Issue 5 (October 2019) - Chen, Ruoying
Abstract: The boom of dockless share bikes in China has brought about enormous private benefits and social benefits. However, it has also imposed upon the public a new cost which can be termed as "bike litter" 1 : share bikes parked or abandoned in pathways, rivers and other public spaces. It has not only damaged the aesthetic value of cities but has created serious safety hazards and public nuisances. None of the conventional methods of regulating road and traffic safety hazards, such as private actions, public enforcement and self-regulation, seem to have stopped bike-litter without also stopping dockless bike services. Without having to stop such services, or overly burdening their operators, it is proposed here that certain obligations should be imposed upon the operators of dockless bike services. Unlike tort-related obligations that focus on results (e.g., the reduction or sanction of bike litter), these new obligations compel operators to establish systems for monitoring the behaviors of bike users. In short, these obligations are as follows: (1) an obligation for operators to mandatorily include provisions in their terms of service to allow the operators to monitor, sanction and rewards certain parking behavior of users of the service; (2) an obligation for operators to create and maintain monitoring systems to detect bike littering and to enforce the user agreements; and (3) an obligation for operators to report on, and disclose, details regarding the operation and effectiveness of these systems. The mandatory disclosure obligation of operators, however, should be strictly subject to the protection of privacy rights of bike riders and the protection of fair competition between different platforms. It is also proposed that these obligations should be created through voluntary agreements between the government regulator and operators under a permit system, rather than by creating new statutory obligations, as the former is much more flexible and allows for the adoption of various incentive schemes. Such an approach may also help regulate torts incidence in other types of platform economies.